E-FARMING IMPLEMENTATION EFFECT ON SUPPLY CHAIN PERFORMANCE OF SUGAR CANE COMMODITIES IN A PLANTATION COMPANY - Aan Fadlianto; Niken Sulistyowati (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2022)
Information technology has been developed by many companies to achieve supply chain performance, E-farming is an application developed to register own sugarcane land/cane people and monitor the progress of plant work based on web and mobile application (android) supported by GIS and satellite technology. The research used is a quantitative method using survey methods through distributing questionnaires to e-farming actors/users at PTPN X. Survey research is research conducted on large and small populations, but the data studied are 352 samples from the population. Analysis using Structural Equation Modeling (SEM) with Smart PLS 3.0 software. The calculation results show that there is a positive and significant effect on the implementation of e-farming on supply chain performance. This means that to improve Supply Chain Performance, it is necessary to increase the role of the application of E-Farming technology, especially application tools can be developed to increase the effectiveness of the company's business processes.